IMPROVING STUDENTS' READING COMPREHENSION THROUGH TASK-BASED INSTRUCTION (A Classroom Action Research in the Eleventh Grade Students of SMA N Kebakkramat in the Academic Year 2008/2009) - Maryati, Sri (2011)
The objectives of the research are (1) to know whether task-based instruction can improve the students' reading comprehension at SMA Negeri Kebakkramat; (2) to know what effects can be established if task-based instruction is used to develop the students' reading comprehension at SMA Negeri Kebakkramat; and (3) to know the strengths and weaknesses of the task-based instruction when it is used to improve the students' reading comprehension at SMA Negeri Kebakkramat. The research was conducted at SMAN Negeri Kebakkramat from February to September, 2009. The method she used is a Classroom Action Research. The subject was the eleventh grade students of SMA Negeri Karanganyar. The data were derived from several techniques including test, observation, interview, and document analysis. To analyse the quantitative data, the writer applied a descriptive statistics, comprising the highest and lowest scores and means. To analyse the qualitative data, the writer applied constant comparative method. The finding reveals that task-based instruction can really improve the students' reading comprehension and other points which can be grouped into: (1) the improvement of students' reading competence; (2) The effects of Task-based instruction; (3) The streghts and weaknesses of Task-based instruction. The research finding of this study implies that task-based instruction can improve the students' reading comprehension well. Therefore the research should be conducted in its order where reflection plays rule to know what should be maintained and what should be revised. Patience, awareness, and creativity are needed when one deals with a study under an action research. The English teachers are suggested to apply task-based instruction technique to improve the students' reading comprehension. The researcher suggests other researchers to develop other points which can be obtained from applying task-based instruction to improve the students' reading comprehension. The result of this study can be a part of input for further study in the hope that they can explore the effectiveness of teaching reading comprehension.